2009
DOI: 10.1021/jp8068909
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ultrafast Photochromic Organometallics and Photoinduced Linkage Isomerization of Arene Chromium Carbonyl Derivatives

Abstract: We review recent studies of processes relevant to photoinduced linkage isomerization of organometallic systems with the goal of preparing organometallics with an efficient and ultrafast photochromic response. The organometallic system thus corresponds to two linkage isomers with different electronic environments that are responsible for different optical properties. Much of this work has focused on examining processes following irradiation of cyclopentadienyl manganese tricarbonyl derivatives (compounds 3-21) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 57 publications
1
56
0
Order By: Relevance
“…The pentacyanonitrosylmetallates show this behavior and Burkey and Heilweil have reported one such organometallic example. [75] The metal nitrosyl compounds feature phototriggered isomerization of the bound nitrosyl ligand from N-bonded to η 2 -NO to Obonded (isonitrosyl). Each isomer is observable by X-ray crystallography and infrared spectroscopy with different decay temperatures.…”
Section: Two-color Photochromesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pentacyanonitrosylmetallates show this behavior and Burkey and Heilweil have reported one such organometallic example. [75] The metal nitrosyl compounds feature phototriggered isomerization of the bound nitrosyl ligand from N-bonded to η 2 -NO to Obonded (isonitrosyl). Each isomer is observable by X-ray crystallography and infrared spectroscopy with different decay temperatures.…”
Section: Two-color Photochromesmentioning
confidence: 99%
“…Alternatively, isomerization from O to S may be achieved by accessing different transition states in the two reactions. [75] The complex [Ru(bpy) 2 …”
Section: Two-color Photochromesmentioning
confidence: 99%
“…[17,18] Heilweil, Webster, Burkey and co-workers have reported one such example in their studies of ultrafast photochromic organometallic compounds. [19] Picosecond transient absorption data for the S-bonded isomer are shown in Figure 2. Initial traces from t = 0 to 10 ps yield the formation of a bleach feature centered at 372 nm, which coincides closely with the ground-state absorbance maximum.…”
Section: (Pic)]mentioning
confidence: 99%
“…Linkage isomerisation is also common in organometallic complexes and ultrafast processes relevant to photoinduced linkage isomerisation in organometallic systems was recently reviewed [52]. Burkey and co-workers have shown that first row organometallic complexes of manganese, ( 5 -C 5 H 4 CH 3 )Mn(CO) 2 (L) with non-chelatable bifunctional ligands (L) undergo linkage isomerisation, following irradiation as shown in Figure 16.…”
Section: For the Earlier Mentioned Compound Fac-[re(bpy)(co)mentioning
confidence: 99%